Storytelling : brewing up a community at Windsor and Eton - O'Brien, Justin ([London] : SAGE, 2016)
Invoking the powerful storytelling vernacular, inspired by Windsor and Eton Brewery's head brewer and case protagonist Paddy Johnson's favoured communication approach, this craft beer case study uses three stories to provide a narrative framework.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Windsor and Eton Brewery; Marketing -- Case studies; Beer industry -- Management -- Case studies; Storytelling -- Case studies; Communication in marketing -- Case studies